Ring current pressure estimation with RAM‐SCB using data assimilation and Van Allen Probe flux data. Issue 23 (9th December 2016) - Godinez, H. C.; Yu, Y.; Lawrence, E.; Henderson, M. G.; Larsen, B.; Jordanova, V. K.
Abstract: Capturing and subsequently modeling the influence of tail plasma injections on the inner magnetosphere is important for understanding the formation and evolution of the ring current. In this study, the ring current distribution is estimated with the Ring Current‐Atmosphere Interactions Model with Self‐Consistent Magnetic field (RAM‐SCB) using, for the first time, data assimilation techniques and particle flux data from the Van Allen Probes. The state of the ring current within the RAM‐SCB model is corrected via an ensemble based data assimilation technique by using proton flux from one of the Van Allen Probes, to capture the enhancement of the ring current following an isolated substorm event on 18 July 2013. The results show significant improvement in the estimation of the ring current particle distributions in the RAM‐SCB model, leading to better agreement with observations. This newly implemented data assimilation technique in the global modeling of the ring current thus provides a promising tool to improve the characterization of particle distribution in the near‐Earth regions. Key Points: Ring current data assimilation helps improve the representation of dynamics for particle distribution Assimilation with Ring current‐Atmosphere Interactions Model (RAM) has potential for better predictive capability of ring current dynamics Van Allen Probe satellites provide crucial information of the state of proton fluxes